O entrelaçamento do psíquico com o corporal em Freud : considerações preliminares sobre o estatuto do campo da psicanálise - Borges, Greicibely Faccin (2011)
The relation between mind and body is a recurring theme not only in the scope of philosophy, but it also has decisive implications for the definition of the scope of the medical sciences and the psychological studies. In this sense, the body concerns medicine, while the mind as conceived by the traditional psychology was understood as the equivalent to conscience, a type of mentalism which excluded the body. If Freud has the merit of systematizing the conception of unconscious mind, what would be the status of this mental field concerning the body? The very way in which Freud conceives the relationship between mind and body is controversal among authors. There are those who point out an identity relationship between mind and body and other ones point out a psychophysical parallelism. So, this work has as its aim to analyze if the entanglement between psychological and physical fields in Freud's work can bestow some preliminary indications about the statutes of the psychoanalytical field. In order to develop the hypothesis, this dissertation was organized in three axes. In way to contextualize the hypothesis, the first axe presents a brief explanation of the discussion regarding mind and body, according to the conception by Descartes, and its possible influences over the constitution on the field of studies in medicine and in psychology. The second axe, by means of notions of representation and affection, makes a preliminary definition about the way Freud, conceived the entanglement between psychological and physical in the study of the neuroses from the very beginning of the psychoanalysis. Those metapsychological indications are deepened in the final axe of the dissertation, which analyses the elements that comprise the conception of instinct [Trieb], in order to indicate how Freud would have circumscribed the field of psychoanalysis. The source of instinct [Trieb], characterized by the erogenous zones, presupposes the body as a sexual, erogenous whole. The transposition of the physical erogeneity to the psychological one, defined by Freud through the conception of instinct [Trieb] reveals that the sexual excitement originated in the body is present and a constitutive part of the mind. Then, the provisory conclusion is that the investigation field delimited by the Freudian psychoanalysis, differently from the traditional conceptions of the body in the medicine and mind in the psychology, would imply an original entanglement between psychological and physical, permeated by erogeneity.